ANALISIS PENGARUH UPAH MINIMUM, INVESTASI DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA DALAM PERSPEKTIF EKONOMI ISLAM - Rasyidah Bulqis Jamaluddin (CV. ALIM'SPUBLISHING, 2023)
Abstract. Absorption of labor is an important problem in national development where the number is increasing from year to year as a result of the increase in population, while the available job opportunities are limited in number, so that the unemployment rate in several cities is increasing. A high level of investment will increase production capacity which will eventually lead to the creation of new jobs. That way, the unemployment rate can be reduced and people's incomes will increase. This research is a quantitative research with secondary data in the 2015-2021 observation period. Data collection in this study uses the documentation method for data on Population 15+ Working, Investment and Minimum Wage obtained from BPS, Department of Manpower and Office of Investment. The collected data is analyzed using multiple linear regression analysis. Overall, the results of multiple linear regression analysis and hypothesis testing can be concluded that partially investment and minimum wages have no significant effect on employment in Indonesia. Simultaneously, it shows that the investment and minimum wage variables have no simultaneous effect on employment in Indonesia. The lack of effect of investment on labor absorption in Indonesia is due to the fact that more investment is channeled into the capital-intensive project sector (services) compared to the labor-intensive project sector, where the capital-intensive project sector absorbs only a small amount of labor. Meanwhile, the minimum wage has no effect on labor absorption because the majority of the working population in Indonesia have received relatively high wages or exceeded the minimum wage. Employment. Absorption of labor in the perspective of Islamic economics is that the government has made various efforts as its responsibility to provide jobs for its people. The essence of Islamic economics in reviewing the power market based on an Islamic perspective shows the potential in generating economic equality in society and realizing prosperity Keywords: national development, Investment, Minimum Wage